Ichnology and sedimentology of the trace fossil-bearing fluvial red beds from the lowermost member of the Paleocene Funing Formation in the Jinhu Depression, Subei Basin, East China. (January 2019) - Zhou, Xuewen; Jiang, Zaixing; Quaye, Jonathan Atuquaye; Duan, Ye; Hu, Chenlin; Liu, Chao; Han, Chao
Abstract: The lowermost member of the Paleocene Funing Formation, which is composed of bioturbated fluvial red beds, is extensively distributed throughout the Jinhu Depression, Subei Basin, East China. Despite its economic value as one of the most important oil-bearing reservoirs in the Subei Basin, the sedimentology, ichnology and paleoenvironment of this formation in the Jinhu Depression remain poorly understood. In this work, we investigated the ichnofossils and sedimentary facies, analyzed the ichnofacies and potential tracemakers and reconstructed the paleoenvironment of the Jinhu Depression based on cores from the lowermost member of the Paleocene Funing Formation. This formation contains a moderately diverse ichnofauna (9 ichnotaxa of the Scoyenia ichnofacies) that includes meniscate burrows ( Taenidium barretti, Taenidium satanassi and Beaconites coronus ), simple horizontal cylindrical burrows ( Palaeophycus tubularis, Palaeophycus heberti and Planolites isp.), simple vertical or subvertical burrows ( Skolithos linearis and Skolithos isp.) and plant root traces. The other complex branched and chambered burrows are left in open nomenclature. These ichnofossils are widespread throughout the three facies associations identified in this study: (1) ephemeral fluvial channel, (2) crevasse splay and (3) distal floodplain facies associations. Multiple lines of sedimentological and ichnological evidence, namely, the predominance of massive and upper flow regime structures, the occurrence of invertebrate burrows (e.g., Skolithos and Taenidium ) in the lower and middle parts of the channel deposits and the dramatic changes in the color and mottling in channel and overbank sediments, indicate that the river discharge was short lived and that the water table was highly variable. The variations in the discharge and water level are attributed to the influence of seasonal rainfall. The cyclic nature of intense rainfall events and dry periods suggests that the Subei Basin was likely located in a semiarid region with a seasonal rainfall pattern during the early Paleocene. This study also reveals that the ephemeral fluvial channel is the facies association with the highest potential to yield oil-bearing reservoirs in the Paleocene red beds of the Jinhu Depression. Additionally, the influence of bioturbation on the reservoir quality in this region should be considered in future research. Highlights: Early Paleocene bioturbated red beds in the Jinhu Depression, Subei Basin, are of ephemeral fluvial origin. A moderately diverse invertebrate ichnofauna (9 ichnotaxa of the Scoyenia ichnofacies) is identified. Three facies associations with poorly distinctive trace fossil assemblages are interpreted. River discharge was ephemeral, and the water table was variable. Semiarid regional climate conditions accompanied by a seasonal rainfall pattern are suggested.